Analyzing the News Coverage of the Marginalized Group of Transgender People in Pakistani Media (Journal of Asian Development Studies, 2024)
The researchers analyzed how Pakistani media report issues relating to transgender people in their routine news coverage. After selecting the reputed English-language newspapers Dawn and The News, the researchers employed content analysis to examine the media approach toward transgender people thoroughly. The findings of the study revealed a 'soft approach' of media toward this marginalized group, as both newspapers highlighted their issue more favorably, supporting the stances of transgender people, especially regarding the security or threats being faced by them. According to Gillig et al. (2018), watching stories about transgender people decreased the [negative] impact of political ideology on the opinions of viewers. As a result, the main findings of this study reflect the supportive attitude toward transgender people in Pakistani media. This approach of media in Pakistan will help to reduce negative perceptions about transgender people because more conservative viewers' perceptions have changed as a result of seeing more positive media representations of these individuals. Nonetheless, there is a need for more positive news coverage because transgender related issues received a minimal amount of coverage—106 news stories over a year in both of the selected newspapers—which appears to be an insufficient amount of coverage of this population.